MANAJEMEN KESISWAAN DI LEMBAGA PENDIDIKAN PADA TINGKAT MADRASAH - Muli Prima Aldi (STAI Nurul Falah Airmolek, 2023)
Student Management is the management of activities that focus on regulation, supervision and service to students, both inside and outside the classroom and starting from the beginning of entry / even before entering to the end / graduation of the institution effectively and efficiently where the point is student management in madrasah help students to develop themselves in accordance with the programs carried out by the madrasa